Savings behavior of college teachers: A comparative study among private and government colleges in Bangladesh - Lina, Rafia Islam; Rahman, Md Habibur; Islam, Md Shamimul (The Economics and Finance Letters, 2025)
The main objectives of a person’s savings are to improve their standard of life, income, and overall financial well-being. The purpose of the research is to comprehend how public and private college teachers manage their finances. The specific goal of the study is to pinpoint and examine the college teachers' savings behavior, motivations, and important factors determining their savings. A set of structured questionnaires was used to gather primary data from 160 government and private college teachers from the Cumilla district of Bangladesh. The gathered data is analyzed using both descriptive and inferential statistics. Findings reveal that teachers are mainly safe to ensure a better future life. The regression result shows that family size and how often people save are negatively related. On the other hand, age, education level, length of service, monthly family income, how often people save, and income from other sources are positively related to annual savings. The study has identified a sharp difference in the motives of savings between government and private college teachers. The length of service, monthly income, and educational qualifications of the college teachers have positive and significant influences on their savings behavior. Policymakers, researchers, and other relevant private-public groups may find the study useful in understanding teachers' savings habits and in taking necessary action to support both the country's economic growth and teachers' financial well-being.